A Caring Approach to Families with Pregnant Women in the Third Trimester Regarding Clean and Healthy Living Behavior in Efforts to Prevent Stunting - Ayu Puspita; I Nyoman Sudyana; Johanna Maria Rotinsulu; Kartika Bungas (Health and Technology Journal (HTechJ), 2025)
Stunting remains a serious challenge in Indonesia, particularly during the third trimester of pregnancy, a critical period for fetal growth. This study aims to analyze the application of a caring approach to families with pregnant women in their third trimester to improve Clean and Healthy Living Behavior (CHLB) as an effort to prevent stunting in Sebangau District. The study was conducted over six months in 2025 using qualitative and quantitative descriptive approaches. Data were collected through participatory observation, in-depth interviews, documentation, and questionnaires distributed to pregnant women and family members. Samples were taken purposively, involving intervention and control groups in six urban villages. Data analysis was conducted using descriptive methods and Principal Component Analysis (PCA) to identify the main components influencing the effectiveness of the caring approach to CHLB and the risk of stunting. The results show that the application of caring dimensions such as emotional, social, and empowerment support has a positive effect on improving CHLB in pregnant women. The dominant influencing factors are family empathy, communication with health workers, and access to sanitation facilities. In conclusion, a caring approach in families can improve CHLB in pregnant women and has significant potential in preventing stunting during pregnancy. The recommendation of this research is the need for integration of caring approaches in public health promotive and preventive programs, as well as the development of caring-based family intervention models that can be implemented at local and national levels.